Smart Metering for Outage Management of Electric Power Distribution Networks. (December 2016) - He, Yan; Jenkins, Nick; Wu, Jianzhong
Abstract: The UK government has committed to the rollout of smart meters for both electricity and gas in all homes and most small businesses by the end of 2020. Outage management of distribution networks is a critical power system application which can get benefits immediately from the large-scale roll-out of smart meters. An outage area identification method based on topology analysis and smart meter information was developed. This method was combined with the smart metering communication models to evaluate the impact of the communication performance of smart metering infrastructure on outage management.